Media studies - Price, Stuart ([S.l.] : Ad Wes Lon Education, 1998)
The market-leading text for A level Media Studies Media Studies is a comprehensive text for A Level and undergraduate students on Media, Communication and Cultural Studies courses. Advertising, television, film, photojournalism, the music industry and other media forms are used to explore the usefulness of theory, from content analysis and semiology, to more recent ideas about discourse and audience. This new edition contains *new sections on radio and deregulation *the 'media violence' debate *press coverage of the 1997 general election *an expanded list of media terms *new work of traditions within semiology *additional studies of music, new technology and news.